Impact of Age on Medication behaviour and Perception Towards Allopathic Medicines: A Comparative Study - NAINWAL, PANKAJ (International Journal of Psychosocial Rehabilitation, 2021)
Medication behavior and perceptions towards allopathic medicines can vary among individuals and are influenced by various factors, including age. Older adults may have different attitudes towards medication use, adherence to prescriptions, and beliefs about medication safety and effectiveness compared to younger individuals. This study aims to compare medication behavior and perception towards allopathic medicines among participants of different age groups. The study can suggest that age is an important factor in medication behavior and perception towards allopathic medicines. Healthcare professionals should consider age-related differences in medication behavior and beliefs when managing patients’ medications. Older adults may need more support to manage their multiple chronic conditions and medication regimens, while younger adults may need education on the safety and effectiveness of allopathic medicines to improve adherence. Future studies could explore other factors that may influence medication behavior and perceptions towards allopathic medicines. The sample size of the study was 187 respondents. The data analysis was performed with the help of t-test and mean.